Management of a Pregnancy with a Solid Pseudopapillary Neoplasm of the Pancreas. (16th April 2018) - Tanacan, Atakan; Orgul, Gokcen; Dogrul, Ahmet Bülent; Aktoz, Fatih; Abbasoglu, Osman; Beksac, M. Sinan
Abstract : A 26-year-old primigravid patient, at 35 weeks and 2 days of gestation, was referred to Hacettepe University Hospital for pancreatic mass, giant cervical myoma, maternal systemic lupus erythematosus, thrombocytopenia, and onset of preterm labor. At 36 weeks and 1 day of gestation (6 days after admission to the hospital), regular uterine contractions started and cervical dilatation with effacement was observed. Because of breech presentation and giant cervical myoma, a cesarean section was performed on the primigravid patient under general anesthesia. Four months after the birth, subtotal pancreatectomy, partial gastrectomy, duodenectomy, cholecystectomy, and omentectomy (Whipple procedure) were performed. The pathologic diagnosis was of a solid pseudopapillary neoplasm of the pancreas; the patient was discharged from hospital after ten days.